Abstracts book of the 13th Arab Congress of Plant Protection, Hammamet, Tunisia, 16-21 October 2022 - Kumari, Safaa; Makkouk, Khaled; Daami-Remadi, Mejda; Najar, Asma; Ben Ghanem, Hajer; Nader, Asaad; Kassem, Mohammad; Moukahel, Abdulrahman (The Arab Society for Plant Protection, 2022)
This Publication is an Abstracts book of the 13th Arab Congress of Plant Protection (13th ACPP), organized by the Arab Society of Plant Protection (ASPP) in collaboration with the Ministry of Agriculture, Water Resources and Fisheries of Tunisia, represented by the National Institute of Agronomic Research of Tunisia (INRAT), held during the period 16-21 October 2022 in Hammamet, Tunisia. The abstracts book contains 371 abstracts (Economic entomology, fungal diseases, bacterial diseases, viral diseases, phytoplasma, nematodes, weeds, chemical pesticides, plant extracts, IPM, biological control, climate change & plant protection, pest surveillance, soil-borne pathogens, food security & plant protection, and other) presented by scientists and graduate students from CWANA Countries, USA and Europe. In addition to the abstracts presented by scientists from the International Organizations such as the Food and Agriculture Organization of the United Nations (FAO), the International Center for Wheat and Maize (CIMMYT), the International Center for Agricultural Research in the Dry Areas (ICARDA), the International Centre for Advanced Mediterranean Agronomic Studies (CIHEAM), the European Plant Protection Organization (EPPO), The Mediterranean Phytopathological Union (MPU), the Arab Center for the Studies of Arid Zones and Dry Lands (ACSAD), the Arab Organization for Agricultural Development (AOAD), and the Islamic Organization for Food Security (IOFS). The abstracts book was Edited by “Safaa G. Kumari, Khaled Makkouk, Mejda Daami-Remadi, Asma Najar, Hajer Ben Ghanem, Nader Asaad, Mohammad Kassem and Abdul Rahman Moukahel”; and published as a special issue of the Arab Journal of Plant Protection (AJPP), Volume 40, October 2022. 127 Pages (English) and 159 Pages (Arabic).